2022
DOI: 10.1111/ene.15348
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of SARS‐Cov‐2 vaccination in patients with myasthenia gravis: A multicenter experience

Abstract: Background and purpose During the COVID‐19 pandemic, myasthenia gravis (MG) patients have been identified as subjects at high risk of developing severe COVID‐19, and thus were offered vaccination with priority. The lack of direct data on the safety and tolerability of SARS‐CoV‐2 vaccines in MG have contributed to vaccine hesitancy. To address this issue, the safety and tolerability of SARS‐CoV‐2 vaccines were assessed in a large cohort of MG patients from two referral centers. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 18 publications
4
29
0
Order By: Relevance
“…In line with Patone et al [ 46 ], we did not find cases of myasthenic exacerbations between the first and second dose, as only three of patients included received ChAdOx1 nCoV-19 vaccine. Our results are very similar to a recent paper by Farina et al that found myasthenic worsening cases in 7.7% of a large group of vaccinated Italian MG patients [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with Patone et al [ 46 ], we did not find cases of myasthenic exacerbations between the first and second dose, as only three of patients included received ChAdOx1 nCoV-19 vaccine. Our results are very similar to a recent paper by Farina et al that found myasthenic worsening cases in 7.7% of a large group of vaccinated Italian MG patients [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent Italian study investigating the safety of anti-SARS-CoV-2 vaccines in 104 myasthenic patients, found MG worsening cases after vaccination in 8/104 (7.7%, 7 after Pfizer BNT162b2 vaccine and 1 after Moderna mRNA-1273 vaccine), most of which were mild events. Remarkably, the frequency of disease exacerbation in anti-MuSK seropositive patients was much higher than other MG categories [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…A small-scale, questionnaire-based study was conducted to assess the early safety of these vaccines, and although reassuring, has not included boosters [ 22 ]. As far as we are aware, only one study has examined the safety of “booster” vaccinations, albeit with a small sample [ 23 ] and without addressing new-onset cases. To the best of our knowledge, no study has been conducted regarding the effect of the Omicron wave on this susceptible population.…”
Section: Introductionmentioning
confidence: 99%
“…The literature so far suggests there may be a 1-15% risk of exacerbation of pre-existing MG following SARS-CoV-2 vaccination, mostly mild and responding well to standard treatment, with the exception of one published case of a patient who suffered a myasthenic crisis one week after the second dose of the Moderna vaccine [ 18 , [39] , [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 99%